Application of the real-time polymerase chain reaction in the detection and enumeration of vibrio cholera from shrimp ponds - Shafillah, binti Sulaiman (Universiti Malaysia Sarawak, UNIMAS, 2013)
Cholera is an enteric disease which causes severe pandemics and it is caused by a bacterium known as Vibrio cholerae. This project focused on the use of real-time PCR to detect and enumerate the presence of V. cholerae from selected shrimp ponds from Asia Aquaculture Sdn. Bhd in Bako Kuching, Sarawak. In this research, repeat in toxin (rtxA) gene was used as the target gene of V. cholerae and the presence of V. cholerae were detected and enumerated of V. cholerae also been done by Real-time PCR. The dynamics of V. cholerae shows a decreasing population during culturing period. The results showed that the V. cholerae population densities was on a decreasing trend with the R2 value in Pond 1 at 0.85, meanwhile R2 value in Pond 14 at 0.68. Thus, it shows a decreasing trend for both shrimp ponds concentration of V. cholerae throughout culturing period. It is believed that real-time PCR assay allows for more rapid detection and identification of V. cholerae which is faster than current conventional assay.